AKTIVITAS PROTEOLITIK BAKTERI ASAM LAKTAT DALAM FERMENTASI SUSU KEDELAI [Proteolytic Activities of Lactic Acid Bacteria in Fermentation of Soymilk] - . Yusmarini; R. Indrati; T. Utami; Y. Marsono (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2010)
Some lactic acid bacteria (LAB) strains had been isolated from spontaneously fermented soymilk which have proteolytic system. The purpose of this research was to study ability of isolates in fermentation of soymilk. The changes in bacterial growth, pH, titrable acidity, and proteolytic activities during fermentation were examined. Isolates of Lactobacillus plantarum 1 R.1.3.2; L. plantarum 1 R.11.1.2 and L. acidophilus FNCC 0051 (as a control) were capable growing in soymilk. The results indicated that initial pH of soymilk was 6,6 and decreased to 4,6 after fermentation and titrable acidity of 0.11 increased to 0.34 after fermentation. The proteolytic activities were 0.352 U/ml – 0.468 U/ml. The electrophoretic pattern of the proteins showed changes during fermentation of soymilk.